Perception and Satisfaction of Residents with the Impact of the Protected Area on Sustainable Tourism - the Case of Deliblatska Peščara Special Nature Reserve, Serbia - Trišić, Igor; Štetić, Snežana; Maksin, Marija; Blešić, Ivana (Geographica Pannonica, 2021)
In the Deliblatska Peščara Special Nature Reserve (SNR) there are a large number of natural and social factors that affect the development of tourism. Such are: rare and endangered endemic flora and fauna that are important in the procedures of species protection, ecosystem, wetlands, socio-cultural heritage, the possibility of developing specific forms of tourism and other factors. The SNR has a relief that is present only in this protected area – dunes. This type of sand has influenced the specific flora and fauna that cannot be found in other areas. There are 18 settlements in the reserve that have significant cultural, monumental and archaeological heritage. The research aims to determine the satisfaction of residents with the function of the SNR in sustainable tourism development using a quantitative methodology and SPSS software. The responses from 510 residents indicate their satisfaction with the development of sustainable tourism in the SNR through ecological, economic and institutional sustainability of this tourism destination.